The regulatory mechanisms and treatment of HDAC6 in immune dysregulation diseases - Liang, Yanyang; Wang, Ying; Xing, Jianxiao; Li, Junqin; Zhang, Kaiming (Frontiers in Immunology, 2025)
Histone deacetylase 6 (HDAC6) is a class IIb histone deacetylase that contains two catalytic domains and a zinc finger ubiquitin binding domain (ZnF-UBP). The deacetylation function of HDAC6 has been extensively studied with well-characterized substrates such as α-tubulin and Hsp90. Apart from its deacetylase activity, HDAC6 ZnF-UBP binds to unanchored ubiquitin of specific sequences and serves as a carrier for transport of aggregated proteins. subsequently, aggresomes is degraded by the autophagy-lysosome pathway. Additionally, Cells can utilize this HDAC6-dependent microtubule transport to assemble and activate inflammasomes, which play a critical role in immune regulation. HDAC6 displays a unique structure and cellular localization as well as diverse substrates, and exhibits a wider range of biological functions than other HDAC isoforms. HDAC6 has been intimately linked to a spectrum of diseases, including rheumatoid arthritis, systemic lupus erythematosus, psoriasis, neuritis, and the cancer immune microenvironment. This review systematically synthesizes the current research advancements of HDAC6, focusing on three key dimensions: the mechanism of action of HDAC6, therapeutic advancements, and translational prospects in clinical applications.